2017
DOI: 10.1016/j.eplepsyres.2017.10.010
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency burst vagal nerve simulation therapy in a natural primate model of genetic generalized epilepsy

Abstract: Purpose Since the approval of Vagal Nerve Stimulation (VNS) Therapy for medically refractory focal epilepsies in 1997, it has been also reported to be effective for a wide range of generalized seizures types and epilepsy syndromes. Instead of conventional VNS Therapy delivered at 20–30 Hz signal frequencies, this study evaluates efficacy and tolerability of high-frequency burst VNS in a natural animal model for genetic generalized epilepsy (GGE), the epileptic baboon. Methods Two female baboons (B1 P.h. Hama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…There are surprisingly no studies evaluating the effects of chronic ASMs on spontaneous seizure activity in the epileptic baboon. Nonetheless, in a recent study, high‐frequency microburst VNS therapy demonstrated efficacy in reducing spontaneous GTCS frequency in epileptic baboons monitored continuously by video …”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 98%
See 3 more Smart Citations
“…There are surprisingly no studies evaluating the effects of chronic ASMs on spontaneous seizure activity in the epileptic baboon. Nonetheless, in a recent study, high‐frequency microburst VNS therapy demonstrated efficacy in reducing spontaneous GTCS frequency in epileptic baboons monitored continuously by video …”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 98%
“…The seizures are mainly myoclonic seizures, and rarely convulsive in character. If convulsive seizures occur, they are usually briefer than the spontaneous GTCS, and may be repetitive . Intramuscular ketamine exceeding 8 mg/kg raises seizure thresholds and suppresses photosensitivity .…”
Section: Results: Nonhuman Primate Models Of Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…All of the baboons had normal gross brain pathology on necropsy. The baboons were participating in three different funded studies at the time of their recordings: two baboons, B1 and B5, were recorded as part of an RNS implantation study, 14 four baboons, B2‐B4 and B7, were recorded as part of a high‐frequency microburst VNS Therapy trial, 15 and one baboon, B6, was implanted with intracranial depth, strip and grid electrodes 9 . The differences between the protocols underlie the disparity of the recording times.…”
Section: Methodsmentioning
confidence: 99%